THE MACROECONOMIC EFFECTS OF BUDGET SPENDING IN AZERBAIJAN’S ECONOMY - ASLANOV, Ilkin (CENTRAL ASIA AND THE CAUCASUS, 2015)
This article analyzes the changes in the amount and structure of budget spending in Azerbaijan’s economy in 2000- 2013. It assesses the impact of budget spending on the dynamics of the economy’s non-oil sector, personal income, employment, poverty, inflation, import, and human development indicators. On the basis of the calculations carried out, it establishes that even if the multiplier of hypothetic spending in the country’s economy is equal to 2.6, the multiplication effect of budget spending amounts to 1.4 in the non-oil sector and 1.8 in personal income, respectively. In addition, a 1% increase in budget spending in real terms leads to a real increase of 0.47% in the non-oil sector and of 0.56% in personal income. Every billion manats of budget spending creates 28,000 new jobs and releases approximately 190-200,000 people from the grips of poverty. At the same time, an abrupt increase in budget spending will stoke inflation and cause an increase in import: a rise in budget spending by 10% increases inflation by 2.1% and import volume by 6.1%.